Resident-focused trauma-informed medical education policies: An environmental scan of Canadian medical schools and partner organizations - Roze des Ordons, Amanda; Kassam, Aliya; Ellaway, Rachel (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2026)
Background: Psychological trauma among resident physicians (residents) is common yet underrecognized, even though it can significantly impact learning, patient care, and well-being. Trauma-informed approaches are one way in which trauma can be mitigated. The purpose of this study was to examine institutional policies related to resident-focused trauma-informed medical education (RF-TIME) at Canadian institutions involved in providing and governing physician training.Methods: We conducted an environmental scan of publicly available online content related to RF-TIME at Canadian medical schools (n = 18) and partner organizations (n = 42), initially focusing on policy, and then broadening our scan to include strategic planning, standards, guidelines, reports, educational documents and support resources. Findings were tabulated and synthesized.Results: We were unable to find RF-TIME-specific policies at any Canadian medical school or partner organization. Thirteen schools briefly mentioned RF-TIME approaches within strategic planning (n = 3 schools), policies not focused on trauma (n = 9), guidelines (n = 1), reports (n = 3), educational resources (n = 3), and/or support resources (n = 8). Seventeen partner organizations included RF-TIME content within strategic planning (n = 2 organizations), standards (n = 2), guidelines (n = 1), reports (n = 9), educational resources (n = 2), and/or support resources (n = 4).Conclusions: Resident-focused policies around trauma-informed approaches to medical education are absent within Canadian institutions and organizations involved in the training and regulation of physicians. Developing and implementing RF-TIME policies may help establish more supportive learning environments for medical trainees with psychological post-traumatic injury.